2020
DOI: 10.4314/jafs.v17i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of productivity of farmland in Imo State

Abstract: The study analysed the determinants of productivity of farmland in Imo State, Nigeria. Primary data were collected using a set of structured  questionnaires from 60 food crop farmers who were selected through purposive and random sampling techniques. Data were analysed using descriptive statistics and econometric tools. The results showed that majority of the respondents were young in their active years, with a mean age of 45 years, married, mostly females, had mean level education of 8 years and mostly farmin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 4 publications
6
3
0
Order By: Relevance
“…This indicates that cassava production and processing is dominated by female farmers in the area. This study is in line with Osuji & Onubuogu (2018) and Anyiam, et al (2019), who found that 56.7% and 70% respectively of farmers in Imo State were females. They averred that female farmers dominated cassava farming because it is regarded as a female crop in some areas of the state.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…This indicates that cassava production and processing is dominated by female farmers in the area. This study is in line with Osuji & Onubuogu (2018) and Anyiam, et al (2019), who found that 56.7% and 70% respectively of farmers in Imo State were females. They averred that female farmers dominated cassava farming because it is regarded as a female crop in some areas of the state.…”
Section: Resultssupporting
confidence: 91%
“…This means that the farmers in this area can be able to understand and apply new techniques involved in cassava farming and value chain processing. This finding is in line with Ehirim et al (2006), Osuji & Onubuogu (2018) and Anyiam, et al (2019), who found in their studies that 94.4%, 96.1% and 100% of farmers in Imo State respectively have a considerable level of education positive to drive changes in their farm practices. This is because farmers' literacy enhances their ability to comprehend and appraise information on farm innovations that improves their farming and yield (Tikon et al, 2023;Apeh, 2018;Onyekuru & Apeh, 2017).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The favorable traits in the indigenous chicken are the ability to withstand harsh weather conditions and diseases. One of the challenges facing the local breeds is that it is smaller in size, and it has a slow growth rate [3]. Many farmers are involved in poultry production, especially in Imo State Nigeria, but the level of productivity remains local and small-scale [4].…”
Section: Introductionmentioning
confidence: 99%